ANTECEDENTS AND CONSEQUENCES OF INSTAGRAM INFLUENCER OPINION LEADERSHIP - Muhammad Alvi Reza; Fatik Rahayu (EBID: Ekonomi Bisnis Digital, 2025)
With increasing consumer awareness particularly among men of the importance of appearance and facial skin health. This growth is also driven by the role of social media and influencers acting as opinion leaders in introducing skincare products to the public. One local brand competing in this market is Kahf, which faces challenges in building consumer loyalty amidst intense market competition. This study adopts a hypothesis testing design to examine the antecedents and consequences of opinion leadership displayed by Instagram influencers. Primary data were collected through a Google Form from 200 Kahf consumers in Jakarta and analyzed using SmartPLS. The findings indicate that perceived originality, perceived uniqueness, and perceived quality have a positive influence on opinion leadership, while perceived quantity does not show a significant effect. Furthermore, opinion leadership is found to have a positive impact on purchase intention, purchase behaviour, and purchase loyalty of Kahf consumers.